A Multi-Level Collaborative and Cooperative Writing Class in Inducing Character Building (A Model of An Integration Between Teaching Writing and Character Education) - TEDI ROHADI (Universitas Widyatama, 2019)
Character education should not plainly implicate socially-authorize pattern for such character as honesty and perseverance, but also and perhaps more importantly it should provide the ways in which the students believe of their own conception selves, and their essential qualities that will back the actualization of those selves. This conceit may require a more personalized or less formulaic appropriate to inscribe instruction, but the compensation of such transformations of instructive goals and methods might well be the revitalization of democratic society in Indonesia. Taking that into account, a multi-level collaborative and cooperative writing class, in a more specific context and scope, classroom practices, provides one of breakthroughs toward this direction. This model of writing class is either implicitly or explicitly integrated with character education. The paper is a report of a research and development. Theories and concepts supporting the study will initiate the paper. The next part of the paper will explore the so called